Implementasi Keamanan Jaringan Menggunakan Metode Port Blocking dan Port Knocking Pada Mikrotik RB-941 (STMIK IKMI Cirebon, 2020)
An important aspect of a network security system is maintaining data integrity and ensuring that it can be used by users safely. All types of attacks and countermeasures against network discovery attempts by unauthorized parties must be able to overcome efforts to protect network security systems. Firewall systems are used to solve this problem, but software-level attack errors cannot be protected by firewall systems. In this study, the implementation of port knocking and port blocking methods in the network was successfully carried out for data privacy issues. The port blocking method on the Mikrotik router permanently blocks the www port and the Winbox port using the services provided by the Mikrotik router. The port knocking method is more effective because it has rules for being able to enter the proxy server and access it remotely on the local network. The port knocking network implementation experiment applied to the Mikrotik router has enforced the winbox port, and www with 1-2-3 authentication flows with each authentication has a predetermined timeout time.